Geophysical Subsoil Characterization and Modeling Using Cluster Analysis for Seismic Microzonation Purposes - Patrizia Capizzi; Raffaele Martorana (Geosciences, 2023)
In the municipality of Enna, 80 HVSR measurements were performed, and some of these were combined with MASW seismic measurements, which made it possible to constrain the data inversion and obtain significant shear wave velocity models. A reconstruction of the depth of the seismic bedrock was performed for the whole territory, showing different depths for the higher and lower areas, as evidenced also by the Vseq parameter map. The frequency peaks identified in the H/V curve were analyzed through a cluster analysis algorithm to evaluate similarities that allow these peaks to be divided according to their stratigraphic origin. A non-hierarchical analysis algorithm modified in such a way as to avoid any a priori choice that could influence the partition has been used. The cluster analysis made it possible to divide the frequency peaks into five groupings, each of which was then associated with a seismic discontinuity, according to the geological contacts expected in the subsoil. Finally, the inversion of the data made it possible to reconstruct the geometries of these geological contact surfaces and to reconstruct a 3D model of the subsoil, which agrees well with the surface geology of the area.